The Political Ethics of Kiai (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2023)
This study focuses on examining the political existence of the Kyai, the values of their political activism as a constructive critique of political dynamics in Indonesia, which in recent years has become increasingly pragmatic. This study uses a type of qualitative research, the data used are primary data and secondary data. After analyzing field data based on the perspective of political sociology theory, this study finds that political pragmatism in Indonesia is currently clearly illustrated along with the increasingly liberal political practices in Indonesia, thus triggering the birth of transactional politics, money politics, and corruption. The populist spirit behind the Kyai's political activism is clearly reflected in their political struggle which tends to fight for two values at once, namely the value of universality and the value of defending personal rights, in this context are human rights and human dignity, as inherited by Gusdur's political thought, Kyai Ahmad Dahlan, Kyai Hasyim Asy'ari, Kyai Sahal Mahfudz and a number of other Kyai figures.